(untitled) - NATO Advanced Research Workshop on Nanomaterials for Application in Medicine and Biology; Giersig, Michael (Dordrecht, 2008)
Includes bibliographical references and index; Biocompatible nanomaterials and nanodevices promising for biomedical applications -- Isohelical DNA-binding oligomers : antiviral activity and application for the design of nanostructured devices -- DNA self-assembling nanostructures induced by trivalent ions and polycations -- DNA-based synthesis and assembly of organized iron oxide nanostructures -- DNA-based nanostructures: changes of mechanical properties of DNA upon ligand binding -- Nanoconstructions based on spatially ordered nucleic acid molecules -- Nanospearing : biomolecule delivery and its biocompatibility -- Multifunctional glyconanoparticles : applications in biology and biomedicine -- Plasmonics of gold nanorods. considerations for biosensing -- Influence of the S-Au bond strength on the magnetic behavior of S-capped Au nanoparticles -- Long-term retention of fluorescent quantum dots in vivo -- Towards polymer-based capsules with drastically reduced controlled permeability -- Polyelectrolyte-mediated transport of doxorubicin through the bilayer lipid membrane -- Network model of acetobacter xylinum cellulose intercalated by drug nanoparticles -- Theoretical approaches to nanoparticles
Keywords: Medical technology -- Congresses; Nanostructured materials -- Congresses; Kỹ thuật y khoa -- Hội thảo; Vật liệu cấu trúc nano -- Hội thảo